Tratamiento Contable en la Empresa Diseño y Construcciones S.A - Bustamante Álvarez, Yuma Astrid (2018)
The present study has the subject of analysis entitled "Accounting Treatment in the Empresa Diseño y Construcciones S.A ", The company whose legal representative is the Architect Raúl Marcelo Villegas Riera, is a legal entity the Ruc: 1293127541001, is It is located on 10 de Agosto Street and Olmedo in the Babahoyo Canton. The mentioned case will be carried out in order to evaluate and analyze the records accountants to obtain adequate information and to be able to detect the problems that have Given erroneous or poorly developed information, it is very important that companies carry a adequate record of its activity, in this case it was corroborated that there are few stocks of an accounting treatment, there is also no correct use of accounting treatment IAS 11, which regulates the accounting treatment and management of construction activities. This deficiency may affect the presentation of the financial statements since the wrong The treatment of the accounts could be affected by poor account manipulation and It would give the real financial situation. This analysis will be carried out with a qualitative methodology that allows us to have a more subjective response, this will be done in the financial department, we also expose that this study is part of the research line of accounting information management. Within the carried out investigation it is mentioned that the main objective is understand the information obtained by the company, the entries and accounting books and the recognition of its accounting treatment for construction activities applying the legal provisions linked to them. This is because at the equator the financial statements prepared can be used for purposes of study or analysis with other entities, even though the states can be similar to those in different countries for the application of IAS and IFRS.